2019
DOI: 10.1175/mwr-d-18-0400.1
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism and Predictability of an Elevated Convection Initiation Event in a Weak-Lifting Environment in Central-Eastern China

Abstract: An elevated convection initiation (CI) of a quasi-linear mesoscale convective system (MCS) that occurred in a weak-lifting environment in the early morning on 23 June 2016 in central-eastern China was investigated using observational analysis and convection-permitting numerical simulations. This MCS gradually developed into a surface-based MCS and eventually produced a strong supercell that spawned an EF4 tornado in Yancheng City of Jiangsu Province and killed 98 people. This elevated MCS was initiated ahead o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…It is a process in which a potentially unstable air parcel passes through its level of free convection (LFC) to initiate buoyant updraft growth with the release of instability. The ability to forecast when and where a new convective system will be initiated is important for disaster preparedness; therefore, CI has been extensively researched in recent decades (e.g., Campbell et al, ; Markowski et al, ; Peters & Hohenegger, ; Su & Zhai, ; Trier et al, ; Weckwerth & Parsons, ; Wilson & Roberts, ; Zhang et al, ; Ziegler & Rasmussen, ). However, predicting the precise location and timing of CI remains a challenge partly due to the lack of spatially and temporally dense observations, especially in the planetary boundary layer (PBL).…”
Section: Introductionmentioning
confidence: 99%
“…It is a process in which a potentially unstable air parcel passes through its level of free convection (LFC) to initiate buoyant updraft growth with the release of instability. The ability to forecast when and where a new convective system will be initiated is important for disaster preparedness; therefore, CI has been extensively researched in recent decades (e.g., Campbell et al, ; Markowski et al, ; Peters & Hohenegger, ; Su & Zhai, ; Trier et al, ; Weckwerth & Parsons, ; Wilson & Roberts, ; Zhang et al, ; Ziegler & Rasmussen, ). However, predicting the precise location and timing of CI remains a challenge partly due to the lack of spatially and temporally dense observations, especially in the planetary boundary layer (PBL).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, following the widely used MCS and CI definition based on radar reflectivity (Romatschke et al., 2010; Trier et al., 2017; Xiao et al., 2017; Zhang et al., 2019), the value of 40 dBZ is used as the reflectivity threshold for the convective precipitation; MCS is identified by a continuous or quasi‐continuous band of 40dBZ reflectivity that extends for at least 50 km in at least one direction; and CI is determined when and where the radar echo first reaches 40 dBZ.…”
Section: Data and Validationmentioning
confidence: 99%
“…Zhang et al. (2019) unveiled mechanisms of an elevated CI by analyzing the thermodynamic environment. They found that the existence of an elevated moist absolutely unstable layer was conducive to the elevated CI, but the dynamic mechanisms were not thoroughly discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In this subsection, we compare major features of atmospheric environment for CCs over the Korean peninsula with those for elevated MCSs over the central US (e.g., Moore et al 2003;Wilson and Roberts 2006;etc. ) and central East China (He et al 2018;Zhang et al 2019). Convection over the front in CCML events may be classified as elevated convection over the cold side of surface boundary.…”
Section: Major Features Of Atmospheric Environment For Ccs Over the Kmentioning
confidence: 99%
“…Recently, He et al (2018) found an occurrence of elevated convection in an event of a nocturnal squall line along the Meiyu Front over central East China, in which the main convection was initiated along a mesoscale convergence line above a stable boundary layer. Zhang et al (2019) showed an elevated MCS that was initiated ahead of a surface front without identifiable boundaries at the surface, and demonstrated that an elevated moist absolutely unstable layer (i.e., a saturated layer within which θ e decreases with height) was found to be conducive to the elevated CI.…”
Section: Introductionmentioning
confidence: 97%